Ultimate strength of precast concrete sandwich panel with opening under axial load - Farah Nora Aznieta, Abdul Aziz; Abang Abdullah, Abang Ali; Mohd Saleh, Jaafar; Abdul Aziz, Abdul Samad; D. N., Trikha (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/